2021
DOI: 10.3390/agriculture11090863
|View full text |Cite
|
Sign up to set email alerts
|

Potato Surface Defect Detection Based on Deep Transfer Learning

Abstract: Food defect detection is crucial for the automation of food production and processing. Potato surface defect detection remains challenging due to the irregular shape of potato individuals and various types of defects. This paper employs deep convolutional neural network (DCNN) models for potato surface defect detection. In particular, we applied transfer learning by fine-tuning a base model through three DCNN models—SSD Inception V2, RFCN ResNet101, and Faster RCNN ResNet101—on a self-developed dataset, and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Compared to our study, their developed VGG model achieved lower recall, precision, and F1-score of 78, 93 and 85% for crack detection in green plums under controlled imaging conditions. However, in another study [13], their developed R-FCN ResNet101 model for scratch detection in potato had a higher precision (98.1%), recall (99%) and F1-score (98.6%) compared with our proposed networks. This could be due to the different conditions used in two studies, e.g., imaging situations, the type of damage and samples, as well as the controlled conditions of trial in the study [13].…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…Compared to our study, their developed VGG model achieved lower recall, precision, and F1-score of 78, 93 and 85% for crack detection in green plums under controlled imaging conditions. However, in another study [13], their developed R-FCN ResNet101 model for scratch detection in potato had a higher precision (98.1%), recall (99%) and F1-score (98.6%) compared with our proposed networks. This could be due to the different conditions used in two studies, e.g., imaging situations, the type of damage and samples, as well as the controlled conditions of trial in the study [13].…”
Section: Resultsmentioning
confidence: 62%
“…Furthermore, [31] reported that YOLO v4 was able to detect apple fruit in a complex environment with recall and an average precision of around 93 and 88%, respectively, compared to Faster R-CNN with 90 and 83%, respectively. The use of R-FCN as a detector and ResNet101 as a feature extractor showed also high values of precision and recall of more than 98% in a study by [13] for potato surface defect detection. However, compared to our study, the images of the fruit were captured in a control situation.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Machine vision inspection has the advantages of economy, objectivity, and high index, which overcome the disadvantages of high labor costs, low efficiency, vague grading standards, and subjectivity of manual expert inspection. It has become a hot research topic in crop shape inspection [ 33 ]. However, existing methods use high-dimensional feature parameters to accurately detect the complex variable shapes of irregular potatoes.…”
Section: Introductionmentioning
confidence: 99%